Fortspinnungstypus revisited : schemata and prototypical features in J. S. Bach's minor-key cantata aria introductions - Rautio, Riitta; Jyväskylän yliopisto (Jyväskylä studies in humanities, ISSN 1459-4323, 2004)
Yhteenveto.
Keywords: Bach, Johann Sebastian, : 1685-1750; Bach, Johann Sebastian, : 1685-1750 : Kantaatit; 1700-luku; 1700-talet; Cantatas, Sacred : Analysis, appreciation; kantaatit; muoto-oppi (musiikki); musiikkianalyysi; alkusoitot; kantater; formlära (musikteori); musikanalys; ouvertyrer; Saksa; Tyskland